Determinan Financial distress Pada Perusahaan Sub-Sektor Ritel Elektronik di Bursa Efek Indonesia - Maria Hendriani; Dean Subhan Saleh; Salsabila Nur Khalisa (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of quick ratio, cash flow from investing activities and Financial Expense on financial distress in an empirical study of electronic retail sub-sector companies listed on the Indonesia Stock Exchange in 2013-2020. This research is a quantitative study that uses secondary data in the form of panel data obtained from the financial statements of companies in the electronic retail sub-sector published on the Indonesia Stock Exchange website. The sampling method used the saturated sample method so that a research sample of 40 financial statements was obtained at 5 companies in the electronic retail sub-sector for an 8-year period, namely 2013-2020. The software used for data processing is Eviews 10. The results show that partially quick ratio has a positive and significant effect on financial distress, while cash flow from investing activities has no effect on financial distress and Financial Expense has a negative effect on financial distress. Simultaneously quick ratio, cash flow from investing activities, Financial Expense affect financial distress.